Design and Modeling for 2D Plate Type MR Damper - Chen, Bingsan; Huang, Dicheng; Li, Chunyu; Chen, Changrong (Frontiers in Materials, 2019)
A two-dimensional magnetorheological damper is developed for the two-dimensional damping requirement in the engineering. The velocity and pressure distribution model of the two-dimensional plate-type damper, also the damping force calculation model are established based on the Navier-Stokes equation. The structural physical parameters are analyzed in theory including the working gap δ, the length a and the width a of the middle slide plate. Experiments have been done to test the damping performance of the two-dimensional plate-type magnetorheological damper on the two-dimensional vibration test-bed, and the effect of the excitation current on the damping performance is analyzed. The experimental results show that the influence of Coulomb damping force on the damping force of magnetorheological damper is great when the appropriate magnetorheological fluid is used. The damping force of magnetorheological damper becomes larger with the increase of excitation current, and the system amplitude is gradually reduced, the maximum reduction of 2.5956 times. It’s confirmed that the design of the two-dimensional plate-type magnetorheological damper is reasonable.